Effectiveness of microcredit for poverty alleviation: evidence from Indonesia - Arp, Frithjof; Ardisa, Alvin (Human Security in the Global South, Ningbo, China, 24-25 February 2016, 2016)
Debate persists about the effectiveness of microcredit for poverty alleviation. We argue that much of this debate is due to discipline-specific research approaches and methodological complexities obscuring fundamental issues. Microfinance organisations do not operate in a vacuum: other forms of collateral-free lending must be taken into account. We illustrate our argument with a study of formal and informal collateral-free lending in the Yogyakarta region of Indonesia. Focused on the fundamental issue of competitive impact, we examine both forms of microcredit through triangulation from multiple perspectives, grounded in the experience of market participants. Importantly, our study includes current and previous borrowing across both formal and informal microcredit. We find two distinct informal schemes used by microbusinesses, both of which successfully compete with formal microfinance, one being perceived as significantly more effective. We also find a mismatch of incentives and strategic objectives in the formal microcredit scheme, compromising its effectiveness. We conceptualise borrower needs and microcredit schemes along financial and operational dimensions, and develop a framework of business and profit logics that helps identify how shifts therein influence the competition scenario. We discuss implications for microfinance policy and practice, and provide suggestions for further research.